2012
DOI: 10.1111/j.1468-3083.2012.04530.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy guided scalp biopsy in cicatricial alopecia

Abstract: The advantage of this method is that it is a fast, precise way to identify even individually affected follicles in early or focal cicatricial alopecia. It also allows for the morphologic characterization of particular follicular structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 14 publications
2
90
0
8
Order By: Relevance
“…[41][42][43][44][45][46] To date, 1-2-mm pale dots, thought to represent fibrous tracts, have been reported on dermoscopic examination of the scalp of persons with afro-textured hair. 44 Although thought to be a sign of scarring (having been observed in both LPP and CCCA), these white dots have also been observed in the setting of nonscarring alopecia, such as AA and pattern hair loss.…”
Section: Dermoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43][44][45][46] To date, 1-2-mm pale dots, thought to represent fibrous tracts, have been reported on dermoscopic examination of the scalp of persons with afro-textured hair. 44 Although thought to be a sign of scarring (having been observed in both LPP and CCCA), these white dots have also been observed in the setting of nonscarring alopecia, such as AA and pattern hair loss.…”
Section: Dermoscopymentioning
confidence: 99%
“…Dermoscopy may aid in selecting the optimal biopsy site. 46 Under specific circumstances other biopsy sites may be chosen, e.g. areas of advanced disease in patients with FPHL to determine follicular density and thus likelihood of response to treatment.…”
Section: Investigationsmentioning
confidence: 99%
“…In fact, it was previously suggested that two packs (compound follicular structures of 2 follicles) are a clue to the diagnosis of lymphocytic cicatricial alopecia on horizontal sections [10] . The presence of peripilar casts is a known dermatoscopic clue of classic LPP [11] , but the presence of compound hairs has only been described in one previous paper [11] , although it can be observed in the images of several reports [6,12] . One possible explanation is that in classic LPP, the fibrosis and inflammation have already destroyed part of the compound follicular structures found in early/subtle LPP.…”
Section: Discussionmentioning
confidence: 84%
“…Klasik, büyük, düzensiz beyaz benekler ise perifolliküler fibrozis alanlarını yansıtan, foliküler yıkımın bir göstergesi olarak kabul edilen trikoskopik bulgulardır (1-3). PSA'lar için tanımlayıcı olup en sık liken planopilariste (LPP) görülürler (1,3,10,12,13).…”
Section: Beyaz Beneklerunclassified
“…Ancak sağlıklı kişilerde de bu bulgu frontal bölgede %25 oranına varacak şekilde saptanabilir (8). PSA'larda erken fibroz bulgusu olarak yaygın sütlü-kırmızı renk değişikliği gözlenebilir, bu görünüm özellikle LPP'de saptanmaktadır (13). Turuncu benekler ise folikül ağızlarına uymayan, sarı beneklerden farklı olarak en az üç kat daha büyük patolojik olarak yüzeyel dermisteki granülomlara uyan renklenmelerdir.…”
Section: Perifoliküler Epidermisunclassified